2019
DOI: 10.1108/mf-01-2017-0018
|View full text |Cite
|
Sign up to set email alerts
|

Capital structure and firm performance in European SMEs

Abstract: Purpose The purpose of this paper is to investigate whether the relationship between capital structure and firm performance in small- and medium-sized enterprises (SMEs) is moderated by credit risk. Design/methodology/approach The authors empirically test whether an SME’s credit risk affects the SME’s relationship between capital structure and firm performance by using a 2012 cross-sectional sample of European SMEs from Austria, Belgium, Finland, France, Germany, Italy, Portugal, Spain, Sweden and the UK. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
65
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 74 publications
(96 reference statements)
7
65
1
1
Order By: Relevance
“…1 SMEs are the units to create new jobs, employment, incomes, new concepts, and innovativeness for an organization of entrepreneurs. 2 In Thailand, the economic system mostly depends on exports of the secondary industries that they are in the strong infrastructures of whole industries, and the heart of them is SMEs. In addition, SMEs in Thailand has also taken evolution and development based on the nation plans and the world economy trends.…”
Section: Introductionmentioning
confidence: 99%
“…1 SMEs are the units to create new jobs, employment, incomes, new concepts, and innovativeness for an organization of entrepreneurs. 2 In Thailand, the economic system mostly depends on exports of the secondary industries that they are in the strong infrastructures of whole industries, and the heart of them is SMEs. In addition, SMEs in Thailand has also taken evolution and development based on the nation plans and the world economy trends.…”
Section: Introductionmentioning
confidence: 99%
“…with debt financing and intuitively get more loans. This biased decision deteriorates the transparent functioning of business operations (Li et al, 2019). Similarly, corporate managers interested in more equity as to get the bonuses from shareholders.…”
Section: Background Of Studymentioning
confidence: 99%
“…It was also found that the liability structure of SMEs is significantly altered towards long-term debts and away from short-term debts. Kang et al (2019) suggest that, for the reason of a more severe asymmetric information problem, SMEs have a higher credit risk than larger firms. It means that the credit risk affects a set of financial activities in general and even more so in SMEs.…”
Section: Literature Reviewmentioning
confidence: 99%